Strategic framework AI-driven HRM, hybrid work, psychological welfare, sustainable talent development, and governance of HR against HR future trends - Ahmad Ridwan; Enni Sustiyatik; Tontowi Jauhari (Goodwood Publishing, 2025)
Purpose: This study aims to develop and empirically validate an integrative strategic framework linking AI-driven HRM, hybrid work, psychological welfare, sustainable talent development, and HR governance in predicting future-ready HR within digitally transforming organizations. Research Methodology: A quantitative approach using SmartPLS-SEM was applied to analyze survey data from 150 HR managers, supervisors, and practitioners across multiple industries in Indonesia. The model evaluated reliability, convergent validity, structural relationships, effect sizes, and predictive relevance. Results: Findings confirm that all five constructs significantly and positively influence future-ready HR. AI-driven HRM improves strategic decision-making and predictive analytics; hybrid work enhances flexibility; psychological welfare strengthens engagement; sustainable talent development builds long-term workforce capability; and HR governance reinforces fairness and ethical practices. The model shows strong explanatory power (R² = 0.713), with all path coefficients significant (p < 0.05). Conclusions: A multidimensional, integrative HRM model is essential for preparing organizations for future challenges. The synergy between technological innovation, employee well-being, continuous talent development, and ethical governance forms the foundation of resilient and future-ready HR systems. Limitations: The study uses a cross-sectional design, a relatively limited sample size, and excludes other potentially relevant predictors such as organizational culture, leadership style, and digital maturity. Contribution: This study advances HRM literature by presenting an empirically validated, holistic model that integrates technology, human factors, and governance, while offering practical guidance for sustainable and human-centered HR strategies.